Architecture of Online Intelligent Counseling System - Mohd Said, Siti Norazilah; Madihie, Amalia; Ng , Giap Weng; Oon , Yin Bee; Lew , Hong Yew; Khan Ullah, Rehman (19th PERKAMA International Counselling Convention, 2013)
This paper introduces the architecture of the Online Intelligent Counseling System or OICSTM. The system is a web-based counseling management system in conjunction to promote counseling services virtually to online users, mainly to Malaysians. The unique of OICSTM is it has counseling appointment scheduling system which the system itself is able to detect the availability of the counseling room and the counselor’s schedule. On top of that, the system allows the users to manage their client documentation in the e-forms menu provided. All forms are secured and verified by both counselor and client where they have a security features. OICSTM also provides electronic counseling services such as counseling via email, psychological testing, counseling products, and counseling academic supervision. For academic purposes, the OICSTM allows communication between supervisor and supervisee. As a result, the system enhances their teaching and learning. To conclude, OICSTM is a trial basis web-based counseling online management system and it is expected to be a high-quality system to help e-counselors or e-counseling educators as well as e-clients as the main system users.